Design and Development of an Exhibition Management System for Final Project Products of Practicum Using the Prototyping Method - Ariyadi, David Juli; Etikasari, Bety (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
This study focuses on the design and development of the Exhibition Management System (EMS) through the Prototyping Method exemplifies a workable solution to the challenges of organizing exhibitions aimed at showcasing products developed from Project Based Learning (PBL) in practicum activities. By integrating features such as participant registration, product submission, feedback collection, and archive management, this system presents an organized platform that boosts user interaction and streamlines operations. Requirement prototype technique of prototyping is utilized because the developer builds the system by outlining its functions and processes, especially when the user or owner of the system is unable to accurately. The system is built using the Laravel framework and MySQL as data storage. This system is not only a digital platform in exhibition management, but also serves as a reference that can be implemented for other educational institutions that want to increase public engagement in the institution's activities to improve the experience through digital solutions. The successful implementation of this system as a benchmark shows its potential to increase innovation, teamwork, and effective results in project-based learning.